The combined application of organic fertilizers improves the physical properties of soil associated to quinoa (Chenopodium quinoa Willd.) cultivation - Bolo Valladares, J.D. (2020)
The reduced acceleration of the organic matter in the soil has been affecting its properties, making it necessary to repeat the use and management of organic fertilizers. The objective of research was to evaluate the effect of two fertilizers application, Island Guano (IG) and sheep manure (SM), on the following three physical properties of the soil: bulk density, water-stable aggregates and penetration resistance, under quinoa (Chenopodium quinoa Willd) cultivation, Hualhuas variety. These properties were determined by beveled cylinder, Yoder wet-sieving and dynamic cone penetrometer methods and under a completely randomized block design, with factorial arrangement of two factors (IG and SM) and three levels per factor (0; 0.5 and 1 t*ha-1 for IG and 0; 2.5 and 5 t*ha-1 for SM), nine treatments were evaluated, with three repetitions, so 27 total experimental units. Results showed that combined application of different doses of IG and SM does not influence bulk density, but with doses IG 0,5 t*ha-1 with SM 5 t*ha-1 and IG 1 t*ha-1 with SM 5 t*ha-1 water-stable aggregates and penetration resistance improved significantly.